Critical care outcomes in patients with pre-existing pulmonary hypertension: insights from the ASPIRE registry. Issue 2 (6th April 2021) - Bauchmuller, Kris; Condliffe, Robin; Southern, Jennifer; Billings, Catherine; Charalampopoulos, Athanasios; Elliot, Charlie A.; Hameed, Abdul; Kiely, David G.; Sabroe, Ian; Thompson, A.A. Roger; Raithatha, Ajay; Mills, Gary H.
Pulmonary hypertension (PH) is a life-shortening condition characterised by episodes of decompensation precipitated by factors such as disease progression, arrhythmias and sepsis. Surgery and pregnancy also place additional strain on the right ventricle. Data on critical care management in patients with pre-existing PH are scarce. We conducted a retrospective observational study of a large cohort of patients admitted to the critical care unit of a national referral centre between 2000–2017 to establish acute mortality, evaluate predictors of in-hospital mortality and establish longer term outcomes in survivors to hospital discharge. 242 critical care admissions involving 206 patients were identified. Hospital survival was 59.3%, 94% and 92% for patients admitted for medical, surgical or obstetric reasons, respectively. Medical patients had more severe physiological and laboratory perturbations than patients admitted following surgical or obstetric interventions. Higher APACHE II (Acute Physiology and Chronic Health Evaluation) score, age and lactate, and lower oxygen saturation measure by pulse oximetry/inspiratory oxygen fraction ( S pO2 / F iO2 ) ratio, platelet count and sodium level were identified as independent predictors of hospital mortality. An exploratory risk score, OPALS (oxygen ( S pO2 / F iO2 ) ≤185; platelets ≤196×10 9 ·L −1 ; age ≥37.5 years; lactate ≥2.45 mmol·L −1 ; sodium ≤130.5 mmol·L −1 ), identified medical patients at increasing risk of hospital mortality. One (11%) out of nine patients who were invasively ventilated for medical decompensation and 50% of patients receiving renal replacement therapy left hospital alive. There was no significant difference in exercise capacity or functional class between follow-up and pre-admission in patients who survived to discharge. These data have clinical utility in guiding critical care management of patients with known PH. The exploratory OPALS score requires validation. Critical care survival is worse in PH patients admitted for medical rather than surgical/obstetric indications. Nevertheless, many show longer term survival and functional recovery. Markers of severity of acute illness at admission are prognostic. https://bit.ly/2YX9Fw9